Decrementally cost-effective health technologies in non-inferiority studies: A systematic review - Darlington, Meryl; Scarica, Raffaele; Chavez-Pacheco, Xyomara; Blamplain Segar, Laeticia; Durand-Zaleski, Isabelle (Frontiers in Pharmacology, 2022)
Background: HTA guidance has generally been driven by situations where innovative and usually more expensive technologies are compared to the prevailing standards of care. Cheaper and less efficacious interventions have received scarce attention, although strategies with minimal individual efficacy losses might produce collective health gains when savings are redistributed. Purpose: This systematic review of health economic evaluations identified interventions that are both cost and outcome reducing to procure a list of candidate decrementally cost-effective technologies. Data Sources: English language searches were performed in PubMed, EMBASE and ClinicalTrials.gov covering 2005 to September 2021. Study Selection: Full economic evaluations reporting in English decrementally cost-effective health technologies based on RCT data, modelling or mixed methods. Data Synthesis: After filtering 4,975 studies found through the systematic database search, 107 decrementally cost-effective health technologies (HTs) were identified. Nearly a third were services (n=29) and similarly for drugs (n=31). For over half of the studies (n=54) health outcomes were measured in QALYs and the cost-utility ratios varied from €140 to €5 million saved per QALY lost, albeit with time horizons varying from four days of follow-up to lifetime extrapolations. Less than a quarter of the studies were carried out from the societal perspective. Limitations: Despite including ClinicalTrials.gov as data source, unpublished studies may have been missed. Conclusions: Our results show a growth in recent years in the number of economic publications demonstrating decrementally cost-effective HTs. Economic tools are needed to facilitate the adoption of such HTs by policy-makers at the national level to maximise health outcomes at the population level.